Consumer perceptions and readiness to adopt “tap & go” card payments in South Africa - Sekhoto, July Motlalepule (University of the Witwatersrand, Johannesburg, 2023)
Payment systems and models are said to be critical in a country’s economy and should a country’s payment systems be problematic then it is likely to affect the stability of the country’s economy. There are new trends in the banking industry which are developing continuously and for businesses to be aligned with these trends it is critically important for marketers, bankers, and business owners to invest and educate consumers on the effectiveness and benefits of using tap & go card payment method. This should also include flexibility in terms of which tap & go payment option to use, whether using a physical card or virtual card. The purpose of this study is to determine the extent to which the eight underlying constructs namely: optimism, innovativeness, convenience, discomfort, insecurity, resistance to change, lack of awareness and perceived risk, affects or impact on consumers’ perception, experiences, and readiness to adopt and use tap & go card payments. The respondents for this study we random people who own a tap & go enabled bank card within South African borders. The data collection method used was in a form of an online survey/questionnaire. The result of the study somehow indicates that, out of the eight constructs only innovativeness and resistance to change showed a bit of a significant impact on consumers’ readiness to adopt and use tap & go card payments. This proves that all other constructs like optimism, convenience, discomfort, insecurity, lack of awareness and perceived risk are somehow insignificant predictors of consumers’ readiness to adopt tap & go card payments. Given the results of this study, marketers, banks, and business owners should consider making consumers aware of different types of tap & go payment systems. Although respondents did not show any level of insecurity or discomfort on adopting and using tap & go card payments, it is still critical for future researchers to pay attention to these two constructs and add information privacy and cyber security as other constructs to determine how comfortable consumers are transacting using cashless methods like tap & go payment method. Several countries are working hard to try and move to cashless society, therefore South African banks, businesses, government, and business owners should join hands in helping South vii Africa move to cashless. Currently there is a considerable amount of money that is sitting offline, since most consumers still prefer paying for their purchases using cash. Educating consumers and offering them safe and convenient payment options, will help increase the circulation of cash in the system and this will help stabilise out economy
research report submitted in partial fulfillment of the requirements for the degree of Master of Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Cashless purchases/transactions; Cashless society; Perception; Experiences; Readiness to adopt; UCTD; SDG-8: Decent work and economic growth